2004
DOI: 10.1038/sj.cgt.7700727
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effect of adenoviral p53 gene therapy and standard chemotherapy in ovarian cancer cells independent of the endogenous p53 status

Abstract: Clinical adenoviral p53 gene therapy has been shown by us and others to inhibit tumor growth of ovarian cancer with endogenous mutant p53. This study was designed to test the cooperative antitumor effect of standard combination chemotherapy using paclitaxel and carboplatin together with adenoviral p53 gene transfer in the presence of wild-type and mutant p53. Seven ovarian cancer cell lines with mutant p53 and seven ovarian cancer cell lines with wild-type p53 were tested. An E1-deleted adenovirus type 5 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…45 Moreover, this cooperative effect of p53 gene therapy and chemotherapy is independent of the endogenous p53 status. 46 These data reinforce the notion that the cytotoxicity of many anticancer agents may act in part through the wt-p53. …”
Section: Discussionsupporting
confidence: 75%
“…45 Moreover, this cooperative effect of p53 gene therapy and chemotherapy is independent of the endogenous p53 status. 46 These data reinforce the notion that the cytotoxicity of many anticancer agents may act in part through the wt-p53. …”
Section: Discussionsupporting
confidence: 75%
“…Promising preclinical data on the in vitro transfection of wild-type p53 into ovarian cancer cells bearing p53 mutations and into xenograft models, coupled with evidence from phase I trials, led to the introduction of this innovative and encouraging technique for front-line treatment of patients with advanced ovarian cancer. 18,24,25 However, dominantnegative crosstalk between ectopic wild-type p53 and recently identified dominant p53 mutants as well as splice variants of p63 and p73 (frequently overexpressed in ovarian cancers) could seriously compromise the effectiveness of p53 gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…20 This study firstly demonstrated in p53-wild-type mesothelioma cells that augmented p53 ) were injected into the intrapleural cavity of nude mice (n ¼ 6) (day 1) and they were treated as indicated on day 3. Ad-p53 with chemotherapy for mesothelioma Q Li et al expressions produced synergistic anti-tumor effects with CDDP or PEM in most of the cases and even in an orthotopic animal model.…”
Section: Ad-p53 With Chemotherapy For Mesothelioma Q LI Et Almentioning
confidence: 99%